Integra????o dos planos de gerenciamento de res??duos s??lidos e de seguran??a do trabalho para a constru????o civil - Sousa, Marineide Alves de (2012)
Construction industry has been gaining prominence in Brazil, mainly due to the economic growth of this country. The growth of the construction industry sector contributes to the increase of Construction and Demolition Waste (CDW) in landfill sites and clandestine dumps in large cities, as well as to the rise of workplace accidents in construction sites. The main reason for this scenario is the negligence of the building companies and the lack of inspection by the government. The Integration of the Plans for Solid Waste Management and Safety at Work for Civil Construction aims to meet Resolutions 307 and 448 of the National Environment Council (CONAMA), as well as the Regulatory Standards promulgated by the Ministry of Labor and Employment (MTE). These regulations rule and control such situations and establish the pathway for the building companies and the construction workers to deal with policies and practices for the adequate management of CDW and for safety and health at the construction workplace. The methodological approach adopted in this study is guided by the collection of secondary data, that is, knowledge gained from bibliographical review, which includes national and international sources (books, scientific papers and articles, technical reports, online information and specialized magazines), as well as the Brazilian legislation related to the Management of Waste and Health and Workplace Safety at the Construction Site. The main Brazilian pieces of legislation, technical regulations and certifications analyzed were: Law 12.305, published in August, 2nd 2010, which institutes the National Solid Waste Policy; CONAMA Resolution 307, published in July, 5th 2002, which defines guidelines, criteria and procedures for the management of civil construction waste; Brazilian Norms (NBR) related to the issue of Construction Waste Management; Regulatory Standards issued by the Ministry of Labor and Employment, approved by the Ministerial Directive 3.214, from June 8th, 1978; and the LEED Certificate for new buildings and reforms. In order to study the integration of workplace safety management, the recommendations of the Ministry of Labor and Employment Regulatory Standard 18 were followed. In the study design, two scenarios were considered: 1) designing an Integrated Management Plan in the planning phase of the project, before the beginning of the construction works; 2) designing an Integrated Management Plan for ongoing construction works. For ongoing construction works, a checklist was prepared which was used for the situational diagnosis. Also, verification lists of the Health and Safety at the Workplace Programs (PCMAT, PPRA, and PCMSO) were presented. The study focused on structuring the designing procedures of the Integrated Management Plan; however, it did not contemplate the phases of implementation, monitoring, assessment of results and correction of inconsistencies. The results of this study lead to the conclusion that it is possible to design an Integrated Plan for Solid Waste Management and Workplace Safety in Civil Construction, assuring conformity with the legal requisites. The situational diagnosis for ongoing construction works facilitates and accelerates the planning process of the proposed Integrated Plan. Planning in the project phase will make it easier to reduce issues such as additional costs, delays, and contractual or inspection penalties. In the execution phase, capacity-building is essential, because it is in this phase that the waste is actually managed. Awareness and participation of the workers are indispensable for the success of the processes planned. The Integrated Plan meets the Brazilian norms and legislation related to the Management of Construction and Demolition Waste, as well as the basic requirements of National and International Certification Programs. Searching and fostering more efficient processes and technologies for CDW and Health and Safety at the Workplace must be constant.